Potential Interfering Substances and Potentiometric Antioxidant Activity Tests in Food Systems - Aleksey V. Tarasov; Natalia V. Zavorokhina; Olga V. Chugunova (Техника и технология пищевых производств)
The food industry knows a lot of methods to determine the total antioxidant activity. The potentiometric method includes the mediator system of potassium hexacyanoferrates (K3[Fe(CN)6]/K4[Fe(CN)6]) and has proved to be quite effective in assessing the antioxidant activity of food products. This method is simple and cheap but its interference issues still remain understudied. This research covered 30 potential interfering substances in beverages and their reactivity toward the mediator system of potassium hexacyanoferrates. The experiment featured carbohydrates (glucose, fructose, sucrose, lactose, maltose), dyes (E102, E110, E124, E129, E132, E133), preservatives (E210, E221, E222, E223, E236, E260), sweeteners (E420, E421, E950, E952, E954), and acidity regulators (E296, E330, E331iii, E334, E337, E338, E363, E386). The potential and pH were determined by the potentiometric method in a mediator system solution in the absence and presence of the abovementioned substances. Cysteine and ascorbic and gallic acids served as controls. Glucose, sucrose, and maltose did not interfere with the analysis, while fructose and lactose showed an insignificant positive interference of unspecified mechanism. Malic (E296), citric (E330), tartaric (E334), and phosphoric (E338) acids increased the potential of the mediator system by lowering the pH. However, these interference effects were observed only at high concentrations in an electrochemical cell and were leveled after a sixfold dilution. Indigo carmine (E132), sodium sulfite (E221), sodium hydrosulfite (E222), and sodium metabisulfite (E223) were oxidized by potassium ferricyanide and showed significant positive interference. Potassium ferricyanide was capable of oxidizing compounds other than natural antioxidants. The industrial use of indigo carmine is limited due to its poor light stability, while sulfites are popular components in winemaking. Sulfite interference is of particular concern in the analysis of white wines and is typical of other antioxidant activity methods. The obtained data can correct the results of the potentiometric antioxidant activity tests if the concentration of the interfering substance is known.